KEMUDI’s Pursuance of Muslim Identity and its Implications to Malaysian Muslims - Sharifah Noorulhuda Binti Habib Elias (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
KEMUDI or Persatuan Kesedaran Melayu dan Islam (The Malay and Islamic Awareness Association) is a Malaysian based non-governmental organization (NGO) established in 2013. The organization aims to embrace and uphold a discreet Malay-Arab Muslim identity believed as being degraded by colonialism that introduces liberal democracy and capitalism to replace Malay monarchy. This qualitative study involves data collection from social media platforms, library research and semi-structured interviews. The descriptive analytical approach is applied within the organizational framework of Objective, Leadership Structure, Membership, Resource, Strategy and Tactic. The aim is to investigate KEMUDI’s origin, strategy and tactic as well as its variant of Muslim identity. It follows that KEMUDI’s pursuit of Muslim identity incorporates upholding a hybrid Arab ancestry (read: prophetic, ahl al-baytness) as the prerogative of Malay Muslim identity using strategical alliances and tactical series of lectures, publications as well as cultural activities. The Malay Arab Muslim identity is being pursued and maintained, symbiotically, as religiously significant and ethnically privileged to serve political, religious and social pursuits. The implication of KEMUDI’s ethno-religious identity to Malaysian Muslims focuses on three sectors of the National Integrity Plan (NIP); politics, civil society organization (CSO) and religion. It is found that the discreet dual Malay Arab Muslim identity adopted by KEMUDI has its share of commendatory and condemnatory implications on Malaysian Muslims.